Beetles diversity (Order: Coleoptera) of R.E.A.C.H Biodiversity Centre, Cameron Highlands, Pahang, Malaysia - Nurul Ain Sha’ari; Nivaarani Arumugam (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
R.E.A.C.H Biodiversity Centre, Cameron Highlands is surrounded by 16 years old rehabilitated forest. This forest is currently managed by an NGO, Regional Environmental Awareness Cameron Highlands (R.E.A.C.H). A study on the diversity of Coleoptera was conducted at the area from July to August 2016. The beetles were sampled using four methods, namely the light trap, yellow pan trap, pitfall trap and manual collection on two trails. A total of 16 species comprise of 34 individuals from eight families was recorded. The Shannon-Wiener Diversity Index is high with H’=2.51 recorded. The most dominant beetles collected was the Scarabaeidae followed by Carabidae. Other beetles that were obtained are Cerambycidae, Colydiidae, Curculionidae, Lucanidae and Cetoniidae. They are all nocturnal beetles except one species, Thaumastopeus pugnator (Cetoniidae) which is diurnal. Coleopterans presence in this rehabilitated forest showed that the rehabilitation effort was successful as the replanted plants managed to attract the coleopterans. Further study at R.E.A.C.H Biodiversity Centre should be conducted in future to identify the changes in the beetle species composition over time.